2015
DOI: 10.1186/s12931-015-0314-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of YKL-40 expression by corticosteroids: effect on pro-inflammatory macrophages in vitro and its modulation in COPD in vivo

Abstract: BackgroundMacrophages constitute a heterogeneous cell population with pro- (MΦ1) and anti-inflammatory (MΦ2) cells. The soluble chitinase-like-protein YKL-40 is expressed in macrophages and various other cell types, and has been linked to a variety of inflammatory diseases, including COPD. Dexamethasone strongly reduces YKL-40 expression in peripheral blood mononuclear cells (PBMC) in vitro. We hypothesized that: a) YKL-40 is differentially expressed by MΦ1 and MΦ2, b) is decreased by corticosteroids and c) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…60 Moreover, an in vitro study by Kunz et al revealed that dexamethasone strongly inhibited the release of YKL-40 from the population of proinflammatory macrophages that are characterized by classic mechanism of activation, secretion of pro-inflammatory cytokines (eg, IFN-γ, IL-1, IL-6, IL-12) and promotion of Th1 immunity. 116 However, long-term treatment with ICS (30 months) did not significantly change sputum and serum YKL-40 levels in patients with COPD. 116 The lack of change in serum YKL-40 level may result from a low circulating corticosteroid level during ICS treatment.…”
Section: The Effect Of Corticosteroids On Chitinase and Clp Levelsmentioning
confidence: 90%
See 1 more Smart Citation
“…60 Moreover, an in vitro study by Kunz et al revealed that dexamethasone strongly inhibited the release of YKL-40 from the population of proinflammatory macrophages that are characterized by classic mechanism of activation, secretion of pro-inflammatory cytokines (eg, IFN-γ, IL-1, IL-6, IL-12) and promotion of Th1 immunity. 116 However, long-term treatment with ICS (30 months) did not significantly change sputum and serum YKL-40 levels in patients with COPD. 116 The lack of change in serum YKL-40 level may result from a low circulating corticosteroid level during ICS treatment.…”
Section: The Effect Of Corticosteroids On Chitinase and Clp Levelsmentioning
confidence: 90%
“…116 However, long-term treatment with ICS (30 months) did not significantly change sputum and serum YKL-40 levels in patients with COPD. 116 The lack of change in serum YKL-40 level may result from a low circulating corticosteroid level during ICS treatment. 117 In addition, there are data suggesting that lung macrophages from patients with COPD have reduced corticosteroid sensitivity compared with macrophages from smokers without COPD.…”
Section: The Effect Of Corticosteroids On Chitinase and Clp Levelsmentioning
confidence: 90%
“…Concerning the latter, 12, 19, and 33 lethal cardiovascular events occurred in the lower, middle, and upper YKL-40 terciles, respectively. IP-10 terciles showed a moderate correlation with all-cause (35,61, and 73 events per tercile; P < 0.001) and cardiovascular mortality (11,24, and 29 events per tercile; P < 0.008). MCP-1 did not reach significance in any of these categories ( Figure 2, Supplementary Table S4).…”
Section: Correlation Of Ykl-40 With Inflammatory Mediators Albumin Lmentioning
confidence: 92%
“…In in vitro experimental models, expression of CLPs depends on the activation state of macrophages (M1 or M2). YKL-40 expression is elevated during the differentiation process of human macrophages, and macrophage differentiation factors GM-CSF or M-CSF have been shown to induce YKL-40 expression (65,70). It was identified that in human monocyte-derived macrophages, IFNγ and LPS are strong inducers of YKL-40 gene expression (15,67).…”
Section: Macrophages Are a Major Source Of Chitinase-like Proteinsmentioning
confidence: 99%